2011
DOI: 10.3109/17453674.2011.623574
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic ulnar nerve injury after pin fixation and after antegrade nailing of supracondylar humeral fractures in children

Abstract: Background and purposeUlnar nerve injury may occur after pinning of supracondylar fractures in children. We describe the outcome and compare the rates of iatrogenic injuries to the ulnar nerve in a consecutive series of displaced supracondylar humeral fractures in children treated with either crossed pinning or antegrade nailing.MethodsMedical charts of all children sustaining this fracture treated at our department between 1994 and 2009 were retrospectively reviewed regarding the mode of treatment, demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
(33 reference statements)
0
24
0
6
Order By: Relevance
“…Persistent postsurgical pain (PPP) with features of NP has been well described in adults presumably due to inadvertent operative trauma to nervous tissue 28 29. PPP has been reported in children, but the overall incidence, role of NP or relevance of age at the time of surgery is not known 30 31. In adults who had had inguinal hernia repair before 5 years of age, persistent pain was reported in 13.5% in one study 32.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent postsurgical pain (PPP) with features of NP has been well described in adults presumably due to inadvertent operative trauma to nervous tissue 28 29. PPP has been reported in children, but the overall incidence, role of NP or relevance of age at the time of surgery is not known 30 31. In adults who had had inguinal hernia repair before 5 years of age, persistent pain was reported in 13.5% in one study 32.…”
Section: Introductionmentioning
confidence: 99%
“…Open reduction of pediatric supracondylar humerus fractures has been associated with increased complications and poorer outcomes, often reported using the criteria of Flynn et al [3,5,6,9,10,12,13]. Several operative tricks and techniques have been described in the literature, but to our knowledge, no study has been designed to show a decrease in the need for open reduction with these techniques [4,7,11,17]. Our technique of Schanz pin placement in the posterior humeral diaphysis was associated with a reduction in the conversion rate to an open procedure and in operative time without affecting final radiographic alignment or complications.…”
Section: Discussionmentioning
confidence: 73%
“…They concluded that their two minimally invasive reduction techniques were advantageous over conventional open reduction and internal fixation. Eberl et al reported on antegrade nailing of displaced pediatric supracondylar humerus fractures and described 9% ''good'' and 91% ''excellent'' results, according to the LinscheidWheeler score [4]. Prone positioning was described by Fowler and Marsh to assist with fracture reduction, and they reported all fractures healed without loss of reduction [7].…”
Section: Introductionmentioning
confidence: 99%
“…20 % und in manchen Serien sogar mit bis zu 50 % beschrieben [19]. Die Kirschner-Draht-Osteosynthese kann folgende Probleme hervorrufen: Infektionen im Bereich der Pinaustrittsstellen, Perforation der Pinenden (0-17%), die iatrogene Gefäßverletzung (0-3 %), iatrogene Nervenverletzung insbesondere des N. ulnaris (0-5 %) [22], Fehlstellung (1-10 %), Materiallockerung (3-10 %) [1]. Bezüglich des Komplikationsrisikos sollte man zwischen jüngeren Kindern (< 8 Jahre) und präadoleszenten Kindern unterscheiden (9-12 Jahre).…”
Section: Konservative Therapieunclassified